Illuminating Interiors – short retrospective (Invited Paper) - Hrdlík, Milan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
Article brings a new view to light as the common denominator of the Universe. From the "big bang" to the present day is electromagnetic radiation accompanying a permanent feature of all forms of life on Earth. The author attempts to briefly outline the archetype for the interior lighting is daylight sun and blue sky. On this basis, it is looking for the justification of basic rules for lighting of interior spaces.
Osvětlování interiérů - Krátká retrospektiva (zvaný příspěvek)
Keywords: interior lighting; human adaptation to Nature